2017
DOI: 10.1016/j.wsj.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Water poverty in upper Bagmati River Basin in Nepal

Abstract: Water Poverty Index (WPI) is a simple and transparent tool to measure water stress at the household and village levels so that local an'd national water agencies can manage problem of access to water, quality and variability; water uses and capacity for water management considering environmental aspects. The research aims to calculate WPI in the upper Bagmati river Basin of Nepal in order to analyse the real water situation in the project area. WPI was estimated using five key components through the consultati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 20 publications
3
51
0
1
Order By: Relevance
“…The DWPI can be attributed to several factors associated with water availability, socioeconomic conditions, environmental implications and the political situation (Coppin and Richards, 1990;Sullivan et al, 2003). DWP mapping is a simple and efficient approach to identify the spatial extent of water-poor/rich areas at different levels of jurisdiction areas (Thakur et al, 2017). This approach has been applied in the analysis of water stresses in many countries all over the world such as the US (James et al, 2007), Nepal (Thakur et al, 2017) and Palestine (West Bank) (Isaac et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DWPI can be attributed to several factors associated with water availability, socioeconomic conditions, environmental implications and the political situation (Coppin and Richards, 1990;Sullivan et al, 2003). DWP mapping is a simple and efficient approach to identify the spatial extent of water-poor/rich areas at different levels of jurisdiction areas (Thakur et al, 2017). This approach has been applied in the analysis of water stresses in many countries all over the world such as the US (James et al, 2007), Nepal (Thakur et al, 2017) and Palestine (West Bank) (Isaac et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…DWP mapping is a simple and efficient approach to identify the spatial extent of water-poor/rich areas at different levels of jurisdiction areas (Thakur et al, 2017). This approach has been applied in the analysis of water stresses in many countries all over the world such as the US (James et al, 2007), Nepal (Thakur et al, 2017) and Palestine (West Bank) (Isaac et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This area is within the Shivapuri-Nagarjun national park and has been protected since 1976 [27] with human activities being limited. The 605 km 2 catchment, upstream of Khokana station (1250 m) mostly comprising the urbanized area of the Kathmandu valley is referred to as the upper catchment [43,49,50]. The 2215 km 2 catchment downstream of Khokana yet upstream of Pandheradovan station (180 m), mostly representing lower/mid mountain region, is referred to as the middle catchment [43,49].…”
Section: Study Areamentioning
confidence: 99%
“…For example, many of the headwater streams in Kathmandu valley, especially during the dry season, are exploited for the purpose of drinking water. Further, the water table in the Kathmandu valley is reported to be lowering substantially due to low recharge and increased extraction of ground water driven by scarcity and low quality of surface water [29,50,57]. Some studies have also reported increasing temperatures in most parts of the catchment [45] which suggests higher rates of evaporation.…”
Section: The Influences Of Rainfall and Lulc Changes On River Dischargementioning
confidence: 99%